Mean Platelet Volume is Affected in Term Fetuses with Intrauterine Growth Restriction - Buyuk, Gul Nihal; Oskovi-Kaplan, Z.Asli; Oksuzoglu, Aysegul; Keskin, H.Levent (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Objectives The aim of our study was to analyze the mean platelet volume levels as a potential marker of altered placentation in intrauterine growth restriction (IUGR) cases.Methods A total of 126 term singleton pregnant women with IUGR fetuses and 345 healthy pregnant controls were recruited and compared.Results The mean platelet volume was significantly higher in the IUGR group (10.8±0.9 fl) than the control group (9.9±1.1 fl) (p=0.03). The mean hemoglobin was lower in IUGR group (11.3 (8.3–14.5) g/dl) than the control group (11.9 (8.2–13.0) g/dl) (p=0.04). The optimal cut-off MPV for prediction of IUGR was ≥10.55 fl, with a sensitivity of 59% and a specificity of 75%.Conclusion Increased MPV levels in term pregnant women may be particularly helpful for discrimination and prediction of high-risk fetuses when IUGR is suspected.
Keywords: intrauterine growth restriction; mean platelet volume; hemoglobin count